PENGARUH JABATAN, PENGEMBANGAN KARIER DAN KEPEMIMPINAN TERHADAP PROFESIONALISME APARATUR PEMERINTAH DAERAH - Andhy Hendro Wijaya; Trilaksono - Nugroho; Timotius - Hartono (Wacana Journal of Social and Humanity Studies, 2009)
ABSTRACT The problems of this research are (1) Is there any relationship between the job analysis towards professionalism of the Local Government officials; (2) Is there any relationship between the career development towards professionalisme of the Local Government officials; (3) Is there any relationship between leadership towards professionalism of the Local Government officials; (4) Is there any relationship between job analysis, career and leadership development simultaneously towards professionalism of the Local Government officials as the implementation demand of the local autonomy. In general, the goal of this research is to provide full and complete descriptions about the existence of personal abilities that are measured based on its professionalism in the Secretariate environment of the Local Government of Gresik Regency to behave the implementation demands of the local autonomy. To understand the fully influence of Job Analysis, Career and Leadership Development towards Professionalism of Local Government of Gresik Regency approached by explanatory research by using quantitative model and operationally the concept of this research are as follows: (1) The Management process of apparatus resources identical with the management concept of human resources and essentially to achieve the organizational goal optimally where the activity of job analysis, the opportunity of career development and the description of leadership situation considered as supporting activities to gain the process of organization activities. (2) Professionalisme is the ability showed by officers in which to complete their job loaded to those officers in accordance with their ability or their expertness. The analysis model used in this research is multipple linear regression analysis because of the limitations of variabel identification as well as independent variables can be directed towards the sharper indicator. The results of this research showed that variables of job analysis provides contribution of 19.46% towards professionalism while the career development variable 26.39%, and leadership variable 31.79%. The professionalism of job implementation was deeply demanded towards all of the Local Government apparatus. The implementation of the local autonomy need some talented and skillful workforces to overcome some emerging problems and meet some new ways to create the organization of the Local Government as a public organization with the main purpose to provide some services to society. The management process of apparatus resources will be expected to be conducted optimally and will be improved continually so that it will create the professional apparatus of the Local Government to implement their jobs.   Keywords: leadership, professionalism, apparature     ABSTRAK Permasalahan dalam penelitian ini adalah (1) Apakah ada hubungan antara analisis jabatan terhadap profesionalisme pejabat Pemerintah Daerah; (2) Apakah ada hubungan antara pengembangan karier terhadap profesionalisme pejabat Pemerintah Daerah; (3) Apakah ada hubungan antara kepemimpinan terhadap profesionalisme pejabat Pemerintah Daerah; (4) Apakah ada hubungan antara analisis jabatan, pengembangan karier dan kepemimpinan secara bersama-sama terhadap profesionalisme pejabat Pemerintah Daerah sebagai tuntutan pelaksanaan otonomi daerah. Secara umum penelitian ini bertujuan memberikan gambaran secara utuh dan lengkap mengenai keberadaan kemampuan personil yang diukur berdasarkan keprofesionalannya di lingkungan Sekretariat Daerah Kabupaten Gresik dalam menyikapi tuntutan pelaksanaan otonomi daerah. Untuk memahami secara utuh Pengaruh Analisis Jabatan, Pengembangan Karier dan Kepemimpinan terhadap Profesionalisme Pejabat Pemerintah Daerah Kabupaten Gresik didekati secara (explanatory research) dengan menggunakan metode kuantitatif dan secara operasional konsep penelitian ini  dinyatakan sebagai berikut: (1)  Proses manajemen sumber daya aparatur identik dengan konsep manajemen sumber daya manusia dan pada hakekatnya untuk mencapai tujuan organisasi secara optimal dimana kegiatan analisis jabatan, peluang pengembangan karier dan penjabaran situasi kepemimpinan merupakan kegiatan pendukung untuk tercapainya proses kegiatan organisasi. (2) Profesionalisme adalah kemampuan yang ditunjukkan oleh pegawai dalam rangka menyelesaikan tugas yang dibebankan kepada pegawai tersebut sesuai dengan kemampuan maupun keahlian yang dimilikinya. Model analisis yang digunakan adalah berbentuk analisis regresi linear berganda karena adanya pembatasan identifikasi variabel bebas maupun variabel tergantung dapat diarahkan kepada indikator yang lebih tajam. Hasil penelitian menunjukkan bahwa variabel analisis jabatan memberikan sumbangan sebesar 19,46% terhadap profesionalisme sedangkan variabel pengembangan karier sebesar 26,39% dan variabel kepemimpinan sebesar 31,79%. Profesionalisme dalam menjalankan tugas sangat dituntut terhadap semua aparatur Pemerintah Daerah. Pelaksanaan otonomi daerah memerlukan tenaga-tenaga yang cukup handal guna mengatasi permasalahan yang timbul dan menemukan terobosan-terobosan baru yang mampu menciptakan organisasi Pemerintah Daerah sebagai organisasi publik dengan tujuan utama pemberian pelayanan kepada masyarakat. Proses manajemen sumber daya aparatur hendaknya dilakukan secara optimal dan dilakukan perbaikan secara terus menerus dengan harapan terciptanya aparatur Pemerintah Daerah profesional dalam menjalankan tugas.   Kata kunci: kepemimpinan, profesionalisme, aparatur pemerintah daerah.